Analisis Perbandingan Konsonan dan Artikulasi Bahasa Prancis dan Bahasa Indonesia - Naswa Nabila Suryanto; Rahma Junita; Yudia Kamila Amalia (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
: Consonants in French have their own uniqueness. To sound each consonant sound in the French language, divided by means of articulation and place of articulation. While phonemes are present during transcription both written and spoken. In written language phonemes can be marked with phonetic symbols, while in spoken language phonemes can be marked with the sound of each phoneme transcribed differently. However, there are times when several consonants are transcribed by the same phoneme: for example the consonant 's' between two vowels is transcribed by a phoneme [2]. it is the same as the consonant 'z' which is indeed transcribed by the phoneme [z]. Consonants such as s, x, z, t are often not read when they are at the end of a word. While the way consonants are articulated in Indonesian is divided into: explosion and friction. When the vocal cords open slightly, then vibrations will occur and will produce sounds, for example /b/, /d/, /g/and/c/. This is in contrast to plosive consonants, voiceless consonants produced when the vocal cords are wide open, so no vibration occurs. For example: /s/, /k/, /p/and/t/. In the case of voiced sounds, consonants in Indonesian are divided into two categories, namely voiced and unvoiced sounds. When the vocal cords vibrate during the process of phoneme sound production and transmission, then the produced consonants of the phoneme type sound. For example: /b/, /c/, /d/, /g/, /z/. Whereas when the vocal cords are open, the vocal cords will not vibrate and the consonants produced are voiceless consonants, for example:/p/, /t/, /k/, /f/, /s/, /∫/.